IMPROVED MATHEMATICAL LEARNING RESULTS OF OPERATING MATERIALS CALCULATE FRACTIONAL NUMBERS THROUGH ETHNOMAMATIC LEARNING GEJOH LESUNG IN CLASS V STUDENTS NGABEAN PONJONG ELEMENTARY SCHOOL STUDENTS - Ganis Nurma Febriarti; Dika Wulandari; Erna Nuryani; Maisaroh Farida Nurrohmah; Mimin Nurnaini Zumaroh (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2022)
Ethnomamatics that associates culture and mathematics certainly have characteristics that support each other. In this paper discussed about how ethnomamatics is appliedto mathematics learning, by associating existing cultural products with the content or concepts of mathematics studied. By looking at various ways of associating culture and mathematics in ethnomamatics, it is characterized by ethnomatteric characteristicsin mathematics learning, especially in learning in schools. This research aims to find out: (1) the learning process of Ethnomamatics Gejoh Lesung on the operating material of calculating fractional fractions of class V in SDN Ngabean Ponjong Gunungkidul Regency, (2) whether the results of learning fractional calculation operating materials can be leveledn through ethnomatematics learning in class V SDN Ngabean Ponjong Gunungkidul Regency. This research instrument is (1) learning outcome tests, (2) student activity observation sheets, (3) observation sheets of learning implementation, and (4) student response questionnaires. Data is analyzed using descriptive analysis. The results showed that: (1) student activity in Ethnomamatics learning Gejoh Lesung based on observations. In cycle II is better because it is in the category of "good" as much as5.56% compared to student activity in the learning process in cycle I which in the category of "sufficient" by 70.55%, (2) at the end of cycle II the observation of observers shows that quantitatively the implementation of learning reachesa core rat valueof 90.05%. Based on the criteria in chapter III meets the criteria "very well" when compared to cycle I which achieves an average score of 80.00% with the criteria "good". (3) Based on the learning outcome score on the initial observation of cycle I and cycle Ishows that many students who have achievedKKM 70 which increased from 27.78% or 5 students at the initial observation to 55.56% or 10 students in cycle I and to 88.89% or 16 students in cycle II.